PRAKTIK PENEGAKAN HUKUM PADA TINDAK PIDANA UJARAN KEBENCIAN (HATE SPEECH) - Ramanatha Disurya (Fakultas Hukum Universitas IBA Palembang, 2019)
Speeches of hate that are sent to someone or a certain group of people have stolen a lot of attention lately. Through posting on social media with the utterance of hatred more and more discussed. The purpose of this study is to find out how the practice of law enforcement practices on crimes of hate speech. This research is a type of legal research which is also referred to as empirical legal research. The results of this study are law enforcement of criminal acts related to hate speech must be carried out in accordance with the laws and regulations that have regulated the crime. Enforcement of criminal law is a criminal justice process. In the criminal justice process, law enforcement officers, both the Police, the General Prosecutor, and the Judge must continue to pay attention to the purpose of the law itself, which must pay attention to justice, benefit, and guarantee legal certainty.